Promotion, Demotion, and Transfer in Human Resource Management in Education: Strategies to Enhance Professionalism and Teaching Quality - Mohammad Irsyad Wira Saputra; Agus Setia Irfandi; Ria Septiana Jaelani; Elizabeth Bryana Stone; Syunu Trihantoyo (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study explores the role of human resource management policies specifically promotion, demotion, and transfer in enhancing professionalism and teaching quality in the education sector. Using a qualitative approach through literature review, the research synthesizes findings from peer-reviewed journals and credible sources. The results highlight that promotion significantly improves educator motivation, job satisfaction, and commitment to professional growth, especially when based on clear performance metrics and transparent procedures. Demotion, when applied fairly and proportionately, functions as a corrective measure to uphold institutional accountability and teaching standards. Meanwhile, transfer policies contribute to organizational agility, equitable workforce distribution, and career development, particularly in addressing staffing imbalances across educational units. The study concludes that these policies are most effective when grounded in competency-based evaluations, supported by ongoing professional development, and implemented through transparent and communicative institutional practices. These strategies not only improve individual performance but also cultivate a dynamic, professional, and high-performing educational environment.